Pengaruh Kualitas Layanan dan Penanganan Keluhan Terhadap Loyalitas Pengguna Dengan Kepuasan Pengguna Sebagai Variabel Intervening (Studi Kasus Aplikasi Bibit Investasi Reksa Dana Syariah)): Studi Kasus Aplikasi Bibit Investasi Reksa Dana Syariah - syafrida, ida; Indrawati, Siti Aisyah (Politeknik Negeri Jakarta, 2024)
This study aims to analyze service quality and handling complaints against user loyalty through user satisfaction as an intervening variable in the millennial generation in Jakarta as users of the Bibit application of sharia mutual funds. This study used a quantitative approach with primary data obtained through questionnaires using the Likert scale as a measurement scale. The author uses the method of path analysis with the SPSS version 25. The results of this study shows that service quality and complaint handling have a positive and significant effect on user satisfaction, service quality has a positive but not significant effect on user loyalty, complaint handling and user satisfaction have a positive and significant effect on user loyalty, user satisfaction is unable to mediate the effect of service quality on user loyalty, and user satisfaction is unable to mediate the effect of complaint handling on the loyalty of Bibit application users sharia mutual fund investment in the millennial generation in Jakarta.